Terceira idade, redes sociais digitais e política: o papel das redes sociais digitais na decisão política da terceira idade - Brassoloto, Matheus Palumbo (Universidade Federal de São Carlos, 2023)
In this study we investigated the impact of virtual social networks, such as Facebook and WhatsApp, on the elderly and how this influences their political perspectives. Seniors are a significant part of the population, and they often face challenges when using these platforms due to unfamiliarity with technology and other barriers. Our objectives included a comprehensive review of the literature on technology, seniors, politics and social media, identifying the obstacles that older people face on social media and analyzing usage patterns, types of interactions and shared content. We explore how older people apply the heuristic model when accessing political information on social media and evaluate the impact of this information on their political perspectives, as well as the effect of fake news and misinformation. We used a comprehensive methodology, combining theoretical review with a questionnaire applied to 64 elderly people. The results revealed that the third Age is quickly adapting to digital technology, with internet and cell phone access widespread. Both WhatsApp and Facebook play essential roles in their lives, being used for social connections and obtaining information. Platforms such as WhatsApp exert significant influence on the political decisions of older people, with family groups playing a crucial role in disseminating political information. We conclude that the relationship between the elderly, virtual social networks and politics is evident and evolving, and we must face challenges related to the dissemination of unverified information and promote digital literacy are crucial to ensure informed and inclusive political participation of those elderly people in the digital age. We recommend future studies to deepen our understanding of these ever-evolving dynamics.
Third age, digital social networks and politics: the role of digital social networks in the political decision-making of the elderly
Keywords: Terceira idade; Facebook; WhastApp; Influência; Decisão política; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO